Gypenosides Alleviate Cone Cell Death in a Zebrafish Model of Retinitis Pigmentosa - Xing Li; Reem Hasaballah Alhasani; Yanqun Cao; Xinzhi Zhou; Zhiming He; Zhihong Zeng; Niall Strang; Xinhua Shu (MDPI AG, 2021)
Retinitis pigmentosa (RP) is a group of visual disorders caused by mutations in over 70 genes. RP is characterized by initial degeneration of rod cells and late cone cell death, regardless of genetic abnormality. Rod cells are the main consumers of oxygen in the retina, and after the death of rod cells, the cone cells have to endure high levels of oxygen, which in turn leads to oxidative damage and cone degeneration. Gypenosides (Gyp) are major dammarane-type saponins of Gynostemma pentaphyllum that are known to reduce oxidative stress and inflammation. In this project we assessed the protective effect of Gyp against cone cell death in the rpgrip1 mutant zebrafish, which recapitulate the classical pathological features found in RP patients. Rpgrip1 mutant zebrafish were treated with Gyp (50 µg/g body weight) from two-months post fertilization (mpf) until 6 mpf. Gyp treatment resulted in a significant decrease in cone cell death compared to that of untreated mutant zebrafish. A markedly low level of reactive oxygen species and increased expression of antioxidant genes were detected in Gyp-incubated mutant zebrafish eyes compared to that of untreated mutant zebrafish. Similarly, the activities of catalase and superoxide dismutase and the level of glutathione were significantly increased in Gyp-treated mutant zebrafish eyes compared to that of untreated mutant zebrafish. Gyp treatment also decreased endoplasmic reticulum stress in rpgrip1 mutant eyes. Expression of proinflammatory cytokines was also significantly decreased in Gyp-treated mutant zebrafish eyes compared to that of untreated mutant zebrafish. Network pharmacology analysis demonstrated that the promotion of cone cell survival by Gyp is possibly mediated by multiple hub genes and associated signalling pathways. These data suggest treatment with Gyp will benefit RP patients.